Can maternal exposure to tamoxifen compromise sperm and behavioural parameters of male rat offspring? - de Matos Manoel, Beatriz; da Silva Moreira, Suyane [UNESP]; Zampieri, Gabriela Morelli [UNESP]; Machado Pinheiro, Luísa [UNESP]; Jorge, Bárbara Campos [UNESP]; Casali Reis, Ana Carolina [UNESP]; Leite Kassuya, Cândida Aparecida; Arena, Arielle Cristina [UNESP] (Elsevier, 2022)
Tamoxifen, a selective non-steroidal estrogen receptor modulator, is the standard adjuvant endocrine treatment for breast cancer. Since information on the risk of using tamoxifen during pregnancy is still scarce, this study evaluated whether the in utero and lactational treatment with this drug could compromise reproductive and behavioural parameters in male offspring. Pregnant Wistar rats were exposed to three doses of tamoxifen (0.12; 0.6; 3 μg/kg), by gavage, from gestational day 15 to lactational day 20. Tamoxifen exposure did not alter the anogenital distance in the male offspring; however, there was a significant increase in the body weight in the 0.12 μg/kg dose and a decrease in the 0.6 μg/kg dose. The male offspring treated with the highest dose exhibited a delay in the onset of puberty, evidenced by an increase in the age of preputial separation. Regarding sperm parameters, there was an increase in the sperm count in the cauda epididymis in the intermediate and highest dose groups, in addition to an increase in the number of static sperm and a decrease in the progressive sperm in the same groups. Moreover, an increase in the number of hyperplasia of the epithelial clear cells was observed in the epididymis. In conclusion, the present study demonstrated that maternal exposure to tamoxifen compromised the installation of puberty of the male offspring and the maturation of the epididymis, affecting sperm storage and motility in the adult life.
Keywords: brain sexual differentiation; epididymis; reproductive parameters; Selective estrogen receptor modulator; sexual development